THE EFFECTIVENESS OF COLLECTION OF LAND AND BUILDING TAX ON REGIONAL TAX REVENUE IN BADUNG REGENCY - Kesuma, Ni Putu Regita Anggraeni; Yuliantari, I Gusti Ayu Eviani (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2023)
Land and building tax is one type of tax that provides benefits and a better socio-economic position for people or entities who have rights to or benefit from the land and buildings. The implementation of land and building taxes through the Regional Revenue Agency can carry out intensification and extensification activities, one of which is to increase effectiveness or optimize existing potential. The problems raised are the effectiveness of land and building tax collection on local tax revenues and the inhibiting factors faced by the Badung Regency Regional Revenue Agency in carrying out land and building tax collection. The aim is to determine the effectiveness of land and building tax collection on local tax revenues and to determine the inhibiting factors faced by the Badung Regency Regional Revenue Agency in carrying out land and building tax collection. The results show that the average percentage of land and building tax collection in Badung Regency reaches 74.82% with less effective criteria. Land and building tax collection that does not reach the target may be caused by a lack of taxpayer discipline, lack of awareness of taxpayers, and arrears in tax payments.